Residual coronary malformation after tibial shaft fracture alters the contact status of the meniscus and cartilage in the knee joint: a computational study - Ding, Kai; Liu, Wei; Sun, Dacheng; Zhang, Yifan; Ren, Chuan; Cheng, Xiaodong; Wang, Haicheng; Zhu, Yanbin; Xing, Xin; Chen, Wei (Frontiers in Surgery, 2024)
ObjectiveThe purpose of this study was to evaluate the effect of residual varus/valgus deformity on the mechanical characteristics of the meniscus and cartilage after tibial shaft fracture.MethodsA finite element model of the lower extremity of a healthy volunteer was constructed from CT and MRI images. The upper and middle tibial fracture models were modified to produce 3°, 5°, and 10° tibial varus/valgus models. For model validation, a patient-specific model with a 10° tibial varus deformity was constructed and simulated under the same boundary conditions.ResultsThe contact area and maximum stress of the normal and modified deformity models were similar to those of the reported studies and a patient-specific model. The maximum stress, contact area, and contact force of the medial tibial cartilage in a normal neutral position were 0.64 MPa, 247.52 mm2, and 221.77 N, respectively, while those of the lateral tibial cartilage were 0.76 MPa, 196.25 mm2, and 146.12 N, respectively. From 10° of valgus to 10° of varus, the contact force, contact area, and maximum stress values of the medial tibial cartilage increased, and those of the lateral tibial cartilage gradually decreased. The maximum stress, contact area, and contact force of the medial tibial cartilage in the normal neutral position were 3.24 MPa, 110.91 mm2, and 62.84 N, respectively, while those of the lateral tibial cartilage were 3.45 MPa, 135.83 mm2, and 67.62 N, respectively. The maximum stress of the medial tibial subchondral bone in a normal neutral position was 1.47 MPa, while that of the lateral was 0.65 MPa. The variation trend of the medial/lateral meniscus and subchondral bone was consistent with that of the tibial plateau cartilage in terms of maximum stress, contact area, and contact force.ConclusionThe residual varus/valgus deformity of the tibia has a significant impact on the mechanical loads exerted on the knee joint. This study provides a mechanical basis and references for the clinical evaluation of tibial fracture reduction and osteotomy for tibial deformity.